Expression changes in the fibulin family in gastric cancer: A Systematic Review - Mahsa mahdizadeh; Zeinab Mohammadi; Seyyed Mehdi jafari (Medical Laboratory Journal)
Background: Gastric cancer (GC) is one of the most widespread gastrointestinal tumors worldwide, with mortality rates among the highest. Globally, we face more than one million newly diagnosed stomach cancer patients every year. Various factors are closely associated with the formation of GC. One of these factors is the change in the level of components of the extracellular matrix in the microenvironment of the stomach tumor. Fibulins are one of the secreted glycoproteins of the extracellular matrix, known as matrix organizers. The purpose of this study was to investigate the changes in fibulins in gastric tumor tissue compared to control samples. Methods: In this systematic review, a search was conducted on June 21, 2024, in alignment with the guidelines set forth by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Scopus, PubMed, and Web of Science databases were searched for articles that examined FBLN gene family and protein expression in patients with GC and GC cell lines. Results: A total of 853 GC tumor samples, ranging from 8 to 197 per study, were analyzed across eight studies published between 2008 and 2023, all conducted in China. Several GC cell lines were also included, such as AGS, Kato III, MKN28, MKN45, SNU1, SNU16, NCI-N87, MGC-803, BGC-823, SGC-7901, and HGC27. Tumor size was reported in four studies, while histopathological grade and lymph node metastasis were each evaluated in four studies. Conclusion: The downregulation of Fibulin-1 and Fibulin-2 supports their potential tumor-suppressive roles in GC, while the upregulation of Fibulin-5 is associated with tumor progression and worse prognosis, making it a candidate biomarker for aggressive disease.